First data on big-scale sand smelt Atherina boyeri Risso, 1810 (Pisces: Atherinidae) from Kılıçkaya Dam Lake, Turkey - Semra Benzer (Journal of Fisheries, 2024)
This research presents primary evidence regarding the occurrence of Atherina boyeri in Kılıçkaya Dam lake. A total of 345 specimens were obtained from local fishermen during May to June 2023. The sampled fish displayed a length range between 50.30 and 94.24 mm and weight between 0.76 and 4.30 g. The study established the length-weight relationship (LWR) based on total length (TL) as W = 0.00002285 L2.7018 for females, W = 0.00003297 L2.6033 for males and W = 0.00002501 L2.6746 for the pooled individuals. The exponential value b of TL-W ratio was determined as 2.6746, indicating negative allometric growth in the species. The average condition factor (CF) was computed as 0.641 ± 0.067. This investigation not only provides initial and valuable insights into the presence of A. boyeri in Kılıçkaya Dam lake but also enhances the understanding of the diversity of aquatic ecosystem. The findings of this study offer practical guidance to local fishery management authorities and decision-makers aiding in the implementation of suitable fishery management strategies to ensure the sustainability of fishery resources.